Pengaruh Pemasaran Media Sosial terhadap Donation Intention pada Platform Crowdfunding - Keysya Puspita Ladyaningtin; Soepatini Soepatini (Penerbit Goodwood, 2025)
Purpose: This study aimed to analyze the influence of social media marketing on donation intention in crowdfunding platforms by involving six key variables: social experience, perceived donor effectiveness, intrinsic and extrinsic donation motivation, strategic positioning, and leveraging creativity. Research Methodology: This research was conducted on the Wecare.id crowdfunding platform using a quantitative survey approach. Data were collected from 237 respondents aged 17–35 years who were active social media users. The data were analyzed using the Partial Least Squares structural equation modeling (PLS-SEM) method with SmartPLS 4 software. Results: The findings indicate that social experience, intrinsic motivation, extrinsic motivation, strategic positioning, and leveraging creativity have significant positive effects on donation intention, while perceived donor effectiveness has no significant effect. Conclusions: Social and motivational factors, combined with strategic and creative marketing, play a crucial role in shaping individuals’ intention to donate through digital platforms. Limitations: This study was limited to one crowdfunding platform (Wecare.id) and focused on a young demographic, which may have affected the generalizability of the findings. Future studies should include other variables such as trust and empathy with more diverse respondents. Contribution: This research extends the application of the Theory of Planned Behavior and Self-Determination Theory in the context of digital donation, providing both theoretical and practical insights for platform managers to design effective social media marketing strategies.